Analysis of Land Use Impacts on Flood Propagation and Inundation Area Using 2D HEC-RAS Modeling: A Case Study of the Babakan Watershed, Central Java - Arief Yudho Wicaksono; Mohammad Farid; Vika Febriyani; Aji Prakoso Nimanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
The Babakan Watershed is located in Brebes Regency, Central Java Province, and represents one of the river systems that experiences recurrent flooding events annually. These events indicate a high vulnerability of the area to changes in hydrological characteristics driven by land use dynamics. This study aims to evaluate the effects of land use change on the hydrological and hydraulic responses of the Babakan Watershed and their implications for flood potential and characteristics. The methodology applies the Soil Conservation Service–Curve Number (SCS–CN) Synthetic Unit Hydrograph approach based on land use data from 2015 and 2022, with the application of a 20-year return period design discharge calibrated against bankfull water level conditions of the Babakan River to ensure consistency with the actual channel capacity. The hydrological analysis results show that the 20-year return period peak discharge (Q20) in 2022, at 274.63 m³/s, is lower than that in 2015, which reached 285.57 m³/s, indicating a reduced flood response associated with land use changes. Integration with hydraulic modeling reveals a decrease in Curve Number (CN), an increase in the percentage of impervious areas reflecting improved watershed infiltration capacity, as well as reductions in flood inundation extent and flow velocity. These findings confirm that integrated hydrological–hydraulic approach is effective for evaluating the impacts of land use change on flood propagation and risk in the Babakan Watershed, while also supporting improved preparedness and watershed management planning for future flood events.